Single-Camera Computer Vision Algorithm for Robot Shortest Path Estimator using morphological structuring element with variable sizes - Hasan, Sami; Th.Yousir, Naeem; S. Jumaa, Shereen (International Journal of Engineering and Technology, 2018)
The robotic challeng of developing and implementing a  shortest-path finding algorithm to reach a destination without bumping into  obstacles has been tackled in this  paper. The proposed algorithm is utilized a single ceiling fixed camera and based on the mask and robot size with different sizes for dilation mask. The implementation has been successfully produced thirty-three computer vision figures and two comparison tables of simulation results by using morphological structuring element with different sizes. This paper’s proposal of optimal path finding algorithm is effeciently save robot energy in reaching targets.